Christmas Eve on Lonesome and Other Stories - Fox, John, Jr., 1862-1919; Yohn, F. C. (Frederick Coffay), 1875-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Christmas Eve on Lonesome and Other Stories" by John Fox, Jr. is a collection of short stories published in the early 20th century that explores themes of love, vengeance, and the complexity of human emotions, all set against the backdrop of the Appalachian region. The opening story introduces a character named Buck, who contemplates his past filled with regret and a desire for revenge as he navigates a snowy landscape during Christmas Eve, only to be confronted by unexpected emotional ties that change the course of his intentions. The beginning of "Christmas Eve on Lonesome" sets a vivid scene as the reader is introduced to Buck, a man haunted by memories of betrayal and the loss of his family, as he prepares to confront an enemy he has longed to punish. As he rides through the snow, Buck$1 (Bs thoughts drift from his vengeance to the light in his enemy's window, which reveals a painful connection to his past: the woman he loved, once thought to be lost to him, is now married to the man he blames for his suffering. As Buck witnesses a child playing in the warm light of that home, he is torn between his desire for retribution and the realization that love and forgiveness may be more potent than hate. This opening sets the tone for the emotional and moral dilemmas that run throughout the collection. (This is an automatically generated summary.)s
Christmas Eve On Lonesome -- The Army Of The Callahan -- The Pardon Of Becky Day -- A Crisis For The Guard -- Christmas Night With Satan.
Release date is 2004-01-01
E-text prepared by Juliet Sutherland, Dave Morgan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Mountain life -- Fiction; Cumberland Mountains -- Fiction; Kentucky -- Social life and customs -- Fiction